THE BACTERIOLOGICAL PROFILE OF LARGE BURN - Stevic M; Vlajkovic A; Jovanovski-Srceva M; Budic I; Marjanovic V; Ristic N; Simic D (My University, 2018)
Background: In case of large burns, there is a high incidence of infections and septicemia associated with high morbidity and mortality. Factors that contribute the most to the emergence of infections are disruption of the skin barrier and severe depression of the immune system. Shock, sepsis and multiple organ failures in burns over 50% TBSA are the leading cause of death. Case description: The retrospective review of three pediatrics patients with deep burns over 50% TBSA, who had been admitted at University Children’s hospital from November 2014 to September 2017, and who survived. The injuries mechanism was identical, the high-voltage current struck them at the top of the train, while they were making a selfie photo. Discussion: The first boy was with 55% TBSA, he spent 60 days in a hospital and had 13 infections. He received 32 anesthesia. Hemoculture was positive 2 times when isolated Staphylococcus haemoliticus and Staphylococcus coagulase negative. Klebsiela pneumoniae was isolated for 5 times, from wound, nose, tube and tracheal aspirate. Acinetobacter baumanii was found 4 times in wound, central vein catheter, and tube. Next patient was with 70% TBSA and the total number of his hospitalization was 88 days. He received 18 anesthesia and had 24 infections. Acinetobacter baumanii was isolated for 18 times, from a wound, urinary catheter, tube and tracheal aspirate. The most common cause of wound infection was Staphylococcus coagulase negative, which was caused in 4 times. The last patient spent in hospital 60 days, TBSA was 64%. During that time he received 15 anesthesia and had in total 42 infections. The most common cause of infections was Acinetobacter baumanii, for 21 times, which was isolated from the wound, urinary catheter, central vein catheter and once from hemoculture. He had wound infection for 21 times, and the most often Proteus mirabilis was isolated. Conclusion: It is necessary to be careful with the use of systemic antibiotics to prevent the formation of resistant bacterial strains. Systemic antibiotics should only be used when there is proven pneumonia, bacteremia, wound infection and urinary infection.